Food Safety and Agro-Environment in China Perceptions and Behaviors of Farmers and Consumers - Nanseki, Teruaki; Song, Min (IntechOpen, 2013)
The prediction of China's rise is the subject of this book. The main ideas of this book are derived from Kanshokufuji, a new concept proposed by the chief editor of Prof. Nanseki, pertaining to a sound food system in a sound agro-environment. It implies that food supply and demand are non-separable in terms of location due to the importance of retaining the suitable condition of the environment and biodiversity in the region. This concept is necessary and useful for coping with environmental issues and related food safety issues. From this view point, several integrated surveys in both rural and urban areas of China were conducted by the food risk research group at the Research Institute for East Asia Environments (RIEAE), Kyushu University to reveal the current status of the environment, food, and agriculture in this country. The results of the surveys are introduced in this book, along with implications and recommendations. We hope this book be referential for policy-makers, researchers and industry personnel relating to food, agriculture and environment.